The cost of providing combined prevention and treatment services, including ART, to female sex workers in Burkina Faso. - Fiona Cianci (PLoS ONE, 2014)
BACKGROUND: Female Sex workers (FSW) are important in driving HIV transmission in West Africa. The Yerelon clinic in Burkina Faso has provided combined preventative and therapeutic services, including anti-retroviral therapy (ART), for FSWs since 1998, with evidence suggesting it has decreased HIV prevalence and incidence in this group. No data exists on the costs of such a combined prevention and treatment intervention for FSW. This study aims to determine the mean cost of service provision per patient year for FSWs attending the Yerelon clinic, and identifies differences in costs between patient groups. METHODS: Field-based retrospective cost analyses were undertaken using top-down and bottom-up costing approaches for 2010. Expenditure and service utilisation data was collated from primary sources. Patients were divided into groups according to full-time or occasional sex-work, HIV status and ART duration. Patient specific service use data was extracted. Costs were converted to 2012 US$. Sensitivity analyses considered removal of all research costs, different discount rates and use of different ART treatment regimens and follow-up schedules. RESULTS: Using the top-down costing approach, the mean annual cost of service provision for FSWs on or off ART was US$1098 and US$882, respectively. The cost for FSWs on ART reduced by 29%, to US$781, if all research-related costs were removed and national ART monitoring guidelines were followed. The bottom-up patient-level costing showed the cost of the service varied greatly across patient groups (US$505-US$1117), primarily due to large differences in the costs of different ART regimens. HIV-negative women had the lowest annual cost at US$505. CONCLUSION: Whilst FSWs may require specialised services to optimise their care and hence, the public health benefits, our study shows that the cost of ART provision within a combined prevention and treatment intervention setting is comparable to providing ART to other population groups in Africa.